The Sale and Use of Second-Hand Clothing in Islamic Law - Tiara Dika Satiti; Muthoifin (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to analyze the sale and use of second-hand clothing from the perspective of Islamic law, with particular attention to the growing practice of trading imported used clothing through social media platforms in Indonesia. The study examines whether such transactions comply with the principles and requirements of Sharia in commercial activities. Theoretical framework: The research is grounded in Islamic commercial jurisprudence (fiqh al-muamalah), emphasizing the principles of lawful trade, transparency, mutual consent, fairness, and the prohibition of uncertainty (gharar) and deception in economic transactions. Literature review: Previous studies generally acknowledge that Islam permits trade and encourages economic activities that fulfill legal and ethical requirements. However, scholars have highlighted concerns regarding transactions involving ambiguity in product quality, quantity, ownership, and condition, particularly in the context of second-hand goods and online commerce. These concerns are closely associated with the concept of gharar, which may undermine transactional justice. Method: This study employs a descriptive qualitative approach. Data were analyzed through a Sharia review of second-hand clothing transactions conducted via Instagram and compared with the realities of market practices. The analysis focuses on the conformity of such transactions with Islamic legal principles governing trade and exchange. Results: The findings indicate that Islam fundamentally permits buying and selling activities, including transactions involving used goods, provided that all contractual pillars and conditions are fulfilled. Nevertheless, the widespread practice of selling imported second-hand clothing in bulk packages often involves items whose quantity, quality, size, and physical condition are unknown to buyers at the time of purchase. This uncertainty creates speculative elements and increases the possibility of deception. Consequently, such transactions may contain gharar and are therefore inconsistent with Sharia principles governing commercial dealings. Implications: The findings encourage traders and consumers to improve transparency and product disclosure in second-hand clothing transactions to ensure Sharia compliance. Novelty: This study contributes by specifically examining Instagram-based imported second-hand clothing transactions through the lens of Islamic commercial law and the concept of gharar.